Parents’ personal growth: expanding the view of therapy for child behavioral problems - Perumbilly, Sebastian A; Anderson, Stephen A; Boylin, William M (Journal of Family Psychotherapy, 2017)
Parenting literature often focuses on parental strategies that promote positive behavioral outcomes for children, but ignores key aspects of parents’ own growth process. This article presents a critical review of current literature on parenting and highlights the importance of focusing on parents’ growth in therapy. A clinical framework to define parents’ growth is offered along with case vignettes and practical guidelines for clinicians in order to assess parents’ growth. © 2017 Taylor & Francis Group, LLC.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-695-656-280-425 tex.type: [object Object]
Keywords: Article; Couple intimacy; behavior therapy; child behavior; child care; child parent relation; dept.mft; education program; family therapy; growth; human; intimacy; medical literature; parental attitude; parenting; parents’ growth; personal growth; personal needs; practice guideline; problem behavior; responsibility; self care; social isolation; training; vignette